AUDITORLIK XULOSASI: ISA 700 “FORMING AN OPINION AND REPORTING ON FINANCIAL STATEMENTS” VA ISA 705–706 TALABLARI (Global Economic Review: Journal of Economics, Policy, and Business Development, 2026)
The article comprehensively examines the process of forming an audit opinion and reporting in accordance with the requirements of International Standards on Auditing ISA 700 (Revised), ISA 705 (Revised), and ISA 706 (Revised). It analyzes types of audit opinions (unmodified, qualified, adverse, disclaimer of opinion), mandatory sections of the auditor’s report, Key Audit Matters, Emphasis of Matter and Other Matter paragraphs, and special requirements applied in cases of modification and emphasis. The relevance of these standards as of 2025 and their practical application are illustrated with examples.